(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the impact of diabetes on oral health, the main dental complications, and measures for their early detection and prevention. It also discusses the importance of cooperation between dentists and endocrinologists.